2018
DOI: 10.1017/s1355617718000619
|View full text |Cite
|
Sign up to set email alerts
|

Memory Strategy Training in Older Adults with Subjective Memory Complaints: A Randomized Controlled Trial

Abstract: Older adults with subjective memory complaints benefit from memory strategy training, especially in their memory functioning in daily life. (JINS, 2018, 24, 1110-1120).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 45 publications
2
66
1
2
Order By: Relevance
“…12 Accordingly, group psychological interventions that benefit psychological well-being and metacognition, along with memory-strategy training, which improves memory functioning in daily-life situations, may be considered. 51,52 This study had limitations. First, the sample of participants with SMCs was relatively small, limiting the power of statistical analyses.…”
Section: Discussionmentioning
confidence: 95%
“…12 Accordingly, group psychological interventions that benefit psychological well-being and metacognition, along with memory-strategy training, which improves memory functioning in daily-life situations, may be considered. 51,52 This study had limitations. First, the sample of participants with SMCs was relatively small, limiting the power of statistical analyses.…”
Section: Discussionmentioning
confidence: 95%
“…Obviously, CityMap offers the possibility to invest more effort and time and to develop a new skill (using environmental support) in order to compensate for less performance (Dixon et al, 2001). As it was shown that older adults compensate for memory decline more successfully when they have higher cognitive reserve available (Frankenmolen et al, 2018), we suggest that cognitive reserve could play an important role in using environmental support for increasing their performance.…”
Section: Discussionmentioning
confidence: 71%
“…This review found 12 RCT studies that addressed subjective memory as an outcome [ 31 , 32 , 34 37 , 40 , 43 45 , 48 , 51 ] and 18 RCT studies that treated objective memory [ 31 , 33 36 , 38 47 , 49 , 50 , 52 ]. The quality of evidence across studies for both outcomes was low (see Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Kruskal-Wallis tests ( H (degree of freedom)) are used to investigate whether dose or duration have an impact on intervention outcome. References of the studies assessing subjective memory [ 31 , 32 , 34 37 , 43 45 , 48 , 51 ], objective memory (all) [ 31 , 33 36 , 38 47 , 49 , 50 , 52 ], objective memory (cognitive only) [ 31 , 33 36 , 42 47 , 49 , 50 , 52 ], executive function and attention [ 31 39 , 41 , 43 , 46 , 47 , 51 , 52 ], global cognition [ 31 , 33 , 38 , 39 , 41 , 43 ], and mood and quality of life [ 31 , 32 , 34 , 35 , 38 , 40 , 41 , 43 , 45 , 46 , 49 , 51 , 52 ]…”
Section: Resultsmentioning
confidence: 99%